2013
DOI: 10.1111/efp.12027
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Australian native annual/herbaceous perennial plant species as asymptomatic or symptomatic hosts of Phytophthora cinnamomi under controlled conditions

Abstract: Summary Phytophthora cinnamomi is a necrotrophic pathogen of woody perennials and devastates many biomes worldwide. A controlled perlite–hydroponic system with no other hyphae‐producing organisms as contaminants present allowed rapid assessment of ten annual and herbaceous perennial plant species most of which have a wide distribution within the jarrah (Eucalyptus marginata) forest in Western Australia where this pathogen has been introduced. As some annuals and herbaceous perennials have recently been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Phytophthora cinnamomi, which was found in six dehesas, either from declining or from non-declining trees, is a primary root pathogen of woody species, considered a hemibiotrophic organism with life strategies which can change from biotrophic to necrotrophic, according to the environmental conditions [53][54][55]. This species is also present in plant reservoirs and, depending on its behavior, will determine if the plant remains asymptomatic or not [54][55][56][57]. Furthermore, P. cinnamomi is highly aggressive to holm oaks, as demonstrated previously [11,12,25,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Phytophthora cinnamomi, which was found in six dehesas, either from declining or from non-declining trees, is a primary root pathogen of woody species, considered a hemibiotrophic organism with life strategies which can change from biotrophic to necrotrophic, according to the environmental conditions [53][54][55]. This species is also present in plant reservoirs and, depending on its behavior, will determine if the plant remains asymptomatic or not [54][55][56][57]. Furthermore, P. cinnamomi is highly aggressive to holm oaks, as demonstrated previously [11,12,25,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…However, P. cinnamomi can change its behaviour when infecting different hosts. It has been observed that it can survive as a biotrophic organism in symptomless hosts, affecting the frequency of detection of the different resistance/reproduction structures between different host species (Crone et al ., ). Therefore, an accurate description of the pathogen behaviour is important for the study of the pathogenicity of P. cinnamomi on Q. ilex .…”
Section: Introductionmentioning
confidence: 97%
“…; Bellgard et al , ). Such structures are important for persistence and survival of other Phytophthora species such as P. cinnamomi (Crone et al , ; Jung et al , ). Roots and vascular tissue that are colonized with P. agathidicida hyphae and oospores are important propagules that readily dislodge from the hosts and disperse through natural movement in free‐flowing water and soil, and can be vectored by humans, animals and vehicles.…”
Section: Phytophthora Agathidicidamentioning
confidence: 99%
“…An important knowledge gap for understanding the basic biology of P. agathidicida and the ecology of kauri dieback is the extent to which P. agathidicida can infect and colonize different plant species in kauri forest, either symptomlessly or as an aggressive primary pathogen. In other forest systems, alternate hosts have been shown to have key ecological roles in the epidemiology of Phytophthora pathogens by acting as sporulating hosts, pathogen refugia, terminal hosts or inoculum bridges (Crone et al , ).…”
Section: Phytophthora Agathidicidamentioning
confidence: 99%